Analysis of Movement Generation for Rice Commodity in West Java Province - Sabrina Mutiara Fajrin; Naissya Shafa Kamila Zahra; Dzakiyyah Yasmin Dzahabiyyah; Dwi Novi Wulansari; Benny Hamdi Rhoma Putra (Journal of Logistics and Supply Chain, 2021)
West Java Province produces several superior commodities, especially in agriculture. Rice production needs to be increased through the movement of the flow of goods effectively and efficiently in logistics activities so that it can increase the rate of the economy in West Java Province. This study aims to analyze rice production on the movement of rice commodities in West Java Province. The research method uses descriptive quantitative methods. The data used in this study are data generated by the movement of rice commodities and data on rice production in West Java Province in 2016. The analytical approach used is linear regression and statistical tests are performed on the regression equation function to test the significance level. Based on the results of linear regression analysis, the function equation is y = 316.21 + 0.16x. It can be concluded that the greater the amount of rice production, the greater the generation of rice commodity movement. In addition, from statistical tests, it can be seen that the amount of rice production has a strong relationship and has a positive and significant linear effect on the rise of the movement of rice commodities in West Java.